The world trading system: Recent trends - Norbert Funke (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
Tariffs no longer represent the most serious impediment to international trade. As the importance of tariffs in restricting free trade has been declining, non-tariff barriers are becoming increasingly important. The use of selected non-tariff barriers is analyzed, focusing on anti-dumping measures, voluntary export restraints, trade related investment measures, and trade related intellectual property rights. Coming multilateral negotiations will have to concentrate on non-tariff barriers. A first prerequisite for successful negotiations is to increase transparency of these instruments. Only if transparency is ensured, improved enforcement mechanisms can be implemented.
Keywords: 330; Nichttarifäre Handelshemmnisse; Antidumping; Direktinvestition; Immaterialgüterrechte; Welt